Symbolic model-checking for resource-bounded ATL - Hoang Nguyen (AAMAS'15: International Conference on Autonomous Agents and Multiagent Systems, 2015)
In this paper we present a symbolic implementation of a model checking algorithm for the verification of properties expressed in Resource-Bounded Alternating Time Temporal Logic (RB-ATL). The implementation is based on the model checker MCMAS. We evaluate the performance of our implementation using simple multi-agent model checking problems of increasing complexity.